Confidence intervals for the mean of lognormal distribution with application - Thongkum, Danupon; Laotrakool, Songmuang; Srisodaphol, Wuttichai (Asia-Pacific Journal of Science and Technology, 2017)
The improved confidence intervals of lognormal distribution are proposed based on Krishnamoorthy and Mathew (2003), and Olsson (2005). The point estimators in each confidence interval are substituted by Jackknife estimator and Bayesian estimator. Coverage Probability and interval width are criterion to compare among the confidence intervals. The results of this comparison are shown in simulation study and real data set.